Selective loss of kisspeptin signaling in oocytes causes progressive premature ovulatory failure - Ruohonen Suvi T; Gaytan Francisco; Gaudi Andrea Usseglio; Velasco Inmaculada; Kukoricza Krisztina; Perdices-Lopez Cecilia; Franssen Delphine; Guler Ipek; Mehmood Arfa; Elo Laura L; Ohlsson Claes; Poutanen Matti; et al. (Oxford Univ Press, 2022)
Study question: Does direct kisspeptin signaling in the oocyte have a role in the control of follicular dynamics and ovulation?
Summary answer: Kisspeptin signaling in the oocyte plays a relevant physiological role in the direct control of ovulation; oocyte-specific ablation of kisspeptin receptor, Gpr54, induces a state of premature ovulatory failure in mice that recapitulates some features of premature ovarian insufficiency (POI).
What is known already: Kisspeptins, encoded by the Kiss1 gene, are essential for the control of ovulation and fertility, acting primarily on hypothalamic GnRH neurons to stimulate gonadotropin secretion. However, kisspeptins and their receptor, Gpr54, are also expressed in the ovary of different mammalian species, including humans, where their physiological roles remain contentious and poorly characterized.
Study design, size, duration: A novel mouse line with conditional ablation of Gpr54 in oocytes, named OoGpr54-/-, was generated and studied in terms of follicular and ovulatory dynamics at different age-points of postnatal maturation. A total of 59 OoGpr54-/- mice and 47 corresponding controls were analyzed. In addition, direct RNA sequencing was applied to ovarian samples from 8 OoGpr54-/- and 7 control mice at 6 months of age, and gonadotropin priming for ovulatory induction was conducted in mice (N = 7) from both genotypes.
Participants/materials, setting, methods: Oocyte-selective ablation of Gpr54 in the oocyte was achieved in vivo by crossing a Gdf9-driven Cre-expressing transgenic mouse line with a Gpr54 LoxP mouse line. The resulting OoGpr54-/- mouse line was subjected to phenotypic, histological, hormonal and molecular analyses at different age-points of postnatal maturation (Day 45, and 2, 4, 6 and 10-11 months of age), in order to characterize the timing of puberty, ovarian follicular dynamics and ovulation, with particular attention to identification of features reminiscent of POI. The molecular signature of ovaries from OoGpr54-/- mice was defined by direct RNA sequencing. Ovulatory responses to gonadotropin priming were also assessed in OoGpr54-/- mice.
Main results and the role of chance: Oocyte-specific ablation of Gpr54 caused premature ovulatory failure, with some POI-like features. OoGpr54-/- mice had preserved puberty onset, without signs of hypogonadism. However, already at 2 months of age, 40% of OoGpr54-/- females showed histological features reminiscent of ovarian failure and anovulation. Penetrance of the phenotype progressed with age, with >80% and 100% of OoGpr54-/- females displaying complete ovulatory failure by 6- and 10 months, respectively. This occurred despite unaltered hypothalamic Gpr54 expression and gonadotropin levels. Yet, OoGpr54-/- mice had decreased sex steroid levels. While the RNA signature of OoGpr54-/- ovaries was dominated by the anovulatory state, oocyte-specific ablation of Gpr54 significantly up- or downregulated of a set of 21 genes, including those encoding pituitary adenylate cyclase-activating polypeptide, Wnt-10B, matrix-metalloprotease-12, vitamin A-related factors and calcium-activated chloride channel-2, which might contribute to the POI-like state. Notably, the anovulatory state of young OoGpr54-/- mice could be rescued by gonadotropin priming.
Large scale data: N/A. .
Limitations, reasons for caution: Conditional ablation of Gpr54 in oocytes unambiguously caused premature ovulatory failure in mice; yet, the ultimate molecular mechanisms for such state of POI can be only inferred on the basis of RNAseq data and need further elucidation, since some of the molecular changes observed in OoGpr54-/- ovaries were secondary to the anovulatory state. Direct translation of mouse findings to human disease should be made with caution since, despite the conserved expression of Kiss1/kisspeptin and Gpr54 in rodents and humans, our mouse model does not recapitulate all features of common forms of POI.
Wider implications of the findings: Deregulation of kisspeptin signaling in the oocyte might be an underlying, and previously unnoticed, cause for some forms of POI in women.
Study funding/competing interest(s): This work was primarily supported by a grant to M.P. and M.T.-S. from the FiDiPro (Finnish Distinguished Professor) Program of the Academy of Finland. Additional financial support came from grant BFU2017-83934-P (M.T.-S.; Ministerio de Economía y Competitividad, Spain; co-funded with EU funds/FEDER Program), research funds from the IVIRMA International Award in Reproductive Medicine (M.T.-S.), and EFSD Albert Renold Fellowship Programme (S.T.R.). The authors have no conflicts of interest to declare in relation to the contents of this work.